Trust and Media: Reflection of the Big Five Factor Personality Traits on COVID-19 Pandemic Communication - İnanç Alikılıç; Özlem Alikılıç; Ebru Gökaliler (Türkiye İletişim Araştırmaları Dergisi)
The pandemic process, in general, is a process that creates anxiety due to reasons such as confusion, instability, misinformation and inadequate planning. Within the scope of this study, the assumption that the personality traits of individuals are effective in getting information and taking the required measures while carrying out the health communication during COVID-19 pandemic, and from the question of whether the individual differences can be associated with the inclination for information receipt or not. This scope of this study aims to measure how the communication of the COVID-19 epidemic towards the Turkish people affects the individuals’ preferences for information, the relationships between the sources they trust, and their individual differences based on the Big-5 factors, within the framework of the five major personality traits. This quantitative study, firstly aims to investigate the information-seeking behavior of the Turkish public in relation to their perceptions of COVID-19 and the impact of messages received from the media. Secondly, it is aimed to measure how the COVID-19 pandemic communication affects the relationships among the media sources they trust in their choices of information. While the trust inhealth care professionals and independent health care associatons were the highest among the individuals who participated in the survey, those who have the responsibility personality trait, trust in the content of COVID-19 messages for government agencies is low.